When green turns costly: The fiscal fallout of EU waste management funds in Italian municipalities - Anna Laura Baraldi; Claudia Cantabene; Alessandro De Iudicibus; Giovanni Fosco; Iacopo Grassi (Ecological Economics, 2026)

Exploring the fatigue phenomenon in individuals with Parkinson’s disease: an Italian multicenter cross-sectional study - Elisabetta Sarasso; Elisa Pelosin; Ilaria Ruotolo; Manuela Maieron; Alessandro Ferrero; Francesca Quarone; Andrea Grassi; Martina Putzolu; Andrea Gardoni; Giovanna Lagravinese; Francesca Di Biasio; Federica Agosta; et al. (Acta Neurologica Belgica, 2026)
Background Fatigue is a common and disabling non-motor symptom in Parkinson’s disease (PD), significantly affecting patients’ quality of life. However, it is often underdiagnosed due to its subjective nature and the lack of a clear definition, hindering the development of effective treatments. Objectives This study aims to investigate the prevalence of fatigue and its associations with sociodemographic factors, disease severity, levodopa equivalent daily dosage (LEDD) and motor, non-motor, and cognitive symptoms in an Italian cohort of patients with PD. Methods An observational cross-sectional study was carried out in three Italian centers from January to May 2024. One hundred PD patients (H&Y ≤ 4) were assessed using validated tools: Parkinson Fatigue Scale (PFS), Fatigue Severity Scale, and Modified Fatigue Impact Scale. Motor and non-motor signs and symptoms, cognitive status, and LEDD were analyzed using non-parametric tests and Spearman’s correlations. Fatigue prevalence was determined based on PFS score ≥ 3.09. Results Fatigue was present in 36% of patients, more prevalent in women and more severe in those with H&Y > 2. Fatigue correlated strongly with non-motor symptoms (MDS-UPDRS Part I; ρ > 0.6, p p p Conclusions Fatigue in PD is a multidimensional phenomenon influenced mainly by non-motor symptoms. Gender-specific differences and the association with disease progression underscore the need of comprehensive and integrated management strategies to address this challenging symptom.

Plant identification in the era of digitalization: opportunities and challenges - Jessica Frigerio; Emily Rose Palm; Giovanni Zecca; Valentina Verduci; Werther Guidi Nissim; Fabrizio Grassi; Massimo Labra (Plant Biosystems, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Attenuation of Cellular Senescence and Improvement of Osteogenic Differentiation Capacity of Human Liver Stem Cells Using Specific Senomorphic and Senolytic Agents - Allancer D. C. Nunes; Louise E. Pitcher; Henry A. Exner; Diego J. Grassi; Brittan Burns; Maria Beatriz Herrera Sanchez; Ciro Tetta; Giovanni Camussi; Paul D. Robbins (Stem Cell Reviews and Reports, 2025)
Expansion of adult stem cells in culture increases the percent of senescent cells, reduces their differentiation capacity and limits their clinical use. Here, we investigated whether treatment with certain senotherapeutic drugs would reduce the accumulation of senescent cells during expansion of human liver stem cells (HLSCs) while maintaining their differentiation capacity. Our results demonstrate that chronic treatment with the senomorphic XJB-5-131 or the senolytics cocktail D + Q reduced the number of senescent cells and significantly reduced the expression of senescence-associated genes and several inflammatory SASP factors in later passage HLSCs. Additionally, treatment with XJB-5-131 and D + Q improved the capacity of HLSCs to undergo osteogenic differentiation following extensive in vitro expansion. Overall, our data demonstrate that treatment with XJB-5-13 or D + Q results in a reduction in the percentage of replication-induced senescent HLSCs and likely other types of adult stem cells and improve the potential therapeutic use of later passage human stem cells. Graphical abstract

Into the backyard: Multiple detections of PCV-2e in rural pig farms of Northern Italy. An unexpected ecological niche? - Giulia Faustini; Claudia Maria Tucciarone; Matteo Legnardi; Laura Grassi; Giacomo Berto; Michele Drigo; Mattia Cecchinato; Giovanni Franzo (Preventive Veterinary Medicine, 2023)

Do changes in Lactuca sativa metabolic performance, induced by mycorrhizal symbionts and leaf UV-B irradiation, play a role towards tolerance to a polyphagous insect pest? - Marco Santin; Valeria Zeni; Arianna Grassi; Renato Ricciardi; Ylenia Pieracci; Filippo Di Giovanni; Sofia Panzani; Christian Frasconi; Monica Agnolucci; Luciano Avio; Alessandra Turrini; Manuela Giovannetti; et al. (Environmental Science and Pollution Research, 2023)
The increased ultraviolet radiation (UV) due to the altered stratospheric ozone leads to multiple plant physiological and biochemical adaptations, likely affecting their interaction with other organisms, such as pests and pathogens. Arbuscular mycorrhizal fungi (AMF) and UV-B treatment can be used as eco-friendly techniques to protect crops from pests by activating plant mechanisms of resistance. In this study, we investigated plant ( Lactuca sativa ) response to UV-B exposure and Funneliformis mosseae (IMA1) inoculation as well as the role of a major insect pest, Spodoptera littoralis . Lettuce plants exposed to UV-B were heavier and taller than non-irradiated ones. A considerable enrichment in phenolic, flavonoid, anthocyanin, and carotenoid contents and antioxidant capacity, along with redder and more homogenous leaf color, were also observed in UV-B-treated but not in AMF-inoculated plants. Biometric and biochemical data did not differ between AMF and non-AMF plants. AMF-inoculated plants showed hyphae, arbuscules, vesicles, and spores in their roots. AMF colonization levels were not affected by UV-B irradiation. No changes in S. littoralis -feeding behavior towards treated and untreated plants were observed, suggesting the ability of this generalist herbivore to overcome the plant chemical defenses boosted by UV-B exposure. The results of this multi-factorial study shed light on how polyphagous insect pests can cope with multiple plant physiological and biochemical adaptations following biotic and abiotic preconditioning.

Investigation of Carnivore protoparvovirus 1 and Amdoparvovirus infections in red fox populations of the Italian Dolomites - Laura Grassi; Maria Luisa Menandro; Federica Obber; Michele Drigo; Matteo Legnardi; Daniela Pasotto; Claudia Maria Tucciarone; Giulia Faustini; Carlo Citterio; Mattia Cecchinato; Giovanni Franzo (Veterinary Research Communications, 2022)

Analysis of A-phase transitions during the cyclic alternating pattern under normal sleep - Martin Oswaldo Mendez; Ioanna Chouvarda; Alfonso Alba; Anna Maria Bianchi; Andrea Grassi; Edgar Arce-Santana; Guilia Milioli; Mario Giovanni Terzano; Liborio Parrino (Medical & Biological Engineering & Computing, 2016)

Efficient synthesis of highly substituted tetrahydroindazolone derivatives - Angela Scala; Anna Piperno; Francesco Risitano; Santa Cirmi; Michele Navarra; Giovanni Grassi (Molecular Diversity, 2015)

Rotavirus Occurrence in Shellfish with Low Levels of E. coli - Francesco Bagordo; Tiziana Grassi; Adele Idolo; Francesca Serio; Giovanni Gabutti; Antonella De Donno (Food and Environmental Virology, 2013)

Aldol-type compounds from water-soluble indole-3,4-diones: synthesis, kinetics, and antiviral properties - Angela Scala; Massimiliano Cordaro; Antonino Mazzaglia; Francesco Risitano; Assunta Venuti; Maria Teresa Sciortino; Giovanni Grassi (Molecular Diversity, 2013)

Detection of Viruses in Coastal Seawater Using Mytilus Galloprovincialis as an Accumulation Matrix - Antonella De Donno; Tiziana Grassi; Francesco Bagordo; Adele Idolo; Francesca Serio; Giovanni Gabutti (Food and Environmental Virology, 2012)

Diastereoselective multicomponent synthesis and anti-HSV-1 evaluation of dihydrofuran-fused derivatives - Angela Scala; Massimiliano Cordaro; Francesco Risitano; Ivana Colao; Assunta Venuti; Maria Teresa Sciortino; Patrizia Primerano; Giovanni Grassi (Molecular Diversity, 2012)

Genetic structure of Rhamnus glaucophylla Sommier endemic to Tuscany - Gianni Bedini; Angelino Carta; Giovanni Zecca; Fabrizio Grassi; Gabriele Casazza; Luigi Minuto (Plant Systematics and Evolution, 2011)

Rotavirus detection in environmental water samples by tangential flow ultrafiltration and RT-nested PCR - Tiziana Grassi; Francesco Bagordo; Adele Idolo; Federica Lugoli; Giovanni Gabutti; Antonella De Donno (Environmental Monitoring and Assessment, 2010)

Spectroscopic properties and related functions of the stigma measured in living cells of Euglena gracilis - Pier Alberto Benedetti; Giovanni Bianchini; Alessandro Checcucci; Romano Ferrara; Sergio Grassi; Dyana Percival (Archives of Microbiology, 1976)